Percutaneous transluminal coronary angioplasty of anomalously originating left coronary artery from right coronary sinus - A case report - Mathew, Dolly (Indian Journal of Case Reports, 2018)
To date, technical experience reported for angioplasty is very limited in patients with anomalous coronary arteries. Balloonangioplasty may be a more favorable approach for revascularization in these vessels. Percutaneous coronary intervention (PCI) inan anomalous left coronary artery (LCA) can be technically difficult because selective cannulation of the vessel may not be easy.We thereby present a case with anterior wall myocardial infarction of an anomalously originated LCA. The PCI was successfullyperformed without severe cardiovascular adverse effects. The earlier unpublished data from our center also suggested that PCI withan anomalous origin of LCA might also be a safe, available, and feasible strategy.